Thyroid Langerhans cell histiocytosis concurrent with papillary thyroid carcinoma: A case report and literature review - Mi, Bin; Wu, Di; Fan, Yue; Thong, Benjamin Ka Seng; Chen, Yudong; Wang, Xue; Wang, Chaofu (Frontiers in Medicine, 2023)
Langerhans cell histiocytosis (LCH) is a clonal neoplasm of myeloid dendritic cells, rarely involving the thyroid gland. Papillary carcinoma (PTC) is the most common histological subtype of thyroid cancer. We report a rare case of a 34-year-old Chinese female who has LCH with thyroid papillary carcinoma (PTC) and cervical lymph node metastasis of LCH, with a review of the literature. The patient has thyroid nodules and cervical lymph node enlargement detected by neck ultrasound during physical examination. Fine needle aspiration cytology (FNAC) showed PTC with Hashimoto's thyroiditis and BRAF V600E mutation. After thyroidectomy and lymph node dissection. Histopathological examination suggests LCH was concurrent with classical PTC, accompanied by LCH cervical lymph node metastasis. No BRAF, HRAS and TERT promoter mutations were detected in LCH metastatic lesions. The patient was in stable clinical condition currently.